Hadith Interpretation and Religious Moderation: A Phenomenological Study among Islamic Religious Education Students in Indonesian Higher Education - Benny Afwadzi; Umi Sumbulah; Nasrulloh Nasrulloh (J-PAI: Jurnal Pendidikan Agama Islam, 2026)
Islamic Religious Education (IRE) students occupy a strategic position as prospective teachers who will shape future generations' religious understanding in Indonesia. While previous studies have strengthened religious moderation through values, pedagogy, and educational ecosystems, limited attention has been given to the epistemological process through which students interpret hadith. This study aims to examine patterns of hadith interpretation among IRE students, identify the primary sources shaping these interpretations, and explore their implications for strengthening religious moderation. Employing a qualitative phenomenological approach, the study involved 120 sixth-semester IRE students from five higher education institutions in East Java, Indonesia. Data were collected through open-ended questionnaires, in-depth interviews, and document analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal three interpretive typologies: textual, semi-textual, and contextual, with the textual typology emerging as the dominant pattern. However, semi-textual and contextual interpretations contribute more substantially to strengthening religious moderation by successfully relating hadith to contemporary issues such as religious extremism and national commitment. The study also finds that formal education is the primary source shaping students' interpretation of hadith, with support from lecturers, religious literature, pesantren, social media, and peer interaction. These findings demonstrate that the contribution of hadith to religious moderation is determined not by the hadith text itself but by the way it is interpreted. They further indicate that strengthening students' interpretive competence is more important than merely introducing hadiths related to religious moderation. This study contributes to the discourse on Islamic Religious Education by positioning hadith interpretation as an epistemological pathway for strengthening religious moderation in higher education.